2003
DOI: 10.1071/ar02095
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids of the sorghum ergot pathogen (Claviceps africana): assay methods for grain and feed and variation between sclerotia/sphacelia

Abstract: Abstract. Assay methods for the alkaloids of sorghum ergot (Claviceps africana) are described and compared. Sorghum ergot bodies (sclerotia/sphacelia) from various regions of Queensland and New South Wales were collected in 1997 and 2001 and assayed by spectrophotometry, thin layer chromatography, or high performance liquid chromatography (HPLC). All contained dihydroergosine (DHES) as the main alkaloid component (about 80%), with smaller amounts of dihydroelymoclavine and festuclavine. The preferred method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…This raised questions of whether Australian isolates of C. africana are more toxigenic than those from other continents. The profile of alkaloids in collections of Australian sphacelia/sclerotia was predominantly DHES (Blaney et al 2003), which is consistent with some African isolates (Frederickson et al 1991). However, the concentrations found in Australian sclerotia varied widely, which could account for variable toxicity.…”
Section: Introductionmentioning
confidence: 48%
See 4 more Smart Citations
“…This raised questions of whether Australian isolates of C. africana are more toxigenic than those from other continents. The profile of alkaloids in collections of Australian sphacelia/sclerotia was predominantly DHES (Blaney et al 2003), which is consistent with some African isolates (Frederickson et al 1991). However, the concentrations found in Australian sclerotia varied widely, which could account for variable toxicity.…”
Section: Introductionmentioning
confidence: 48%
“…The production of all 3 alkaloids was always higher in mycelia than in broth, and there was a clear correspondence between alkaloids in mycelium and broth. The general pattern of alkaloid production observed in sorghum ergot sclerotia from Queensland (Blaney et al 2003) was also observed in these cultures: DHES predominated, with smaller amounts of DHEL and FEST. Alkaloids were not detected in the spent broths from the first incubation in Mantle's medium (<0.01 mg/L), whereas they were present in broth after the second incubation as shown in Table 3.…”
Section: Alkaloid Production By Australian Isolatesmentioning
confidence: 77%
See 3 more Smart Citations